Global governance and the United Nations system - Rittberger, Volker, 1941-2011 (United Nations University Press, 2001)
This work offers an analysis of changing world order at the beginning of the 21st century. It examines the progression from international to global governance, focusing on the fundamental change of actors, agendas, collective decisionmaking, and the role of the UN system.